Effect of Moringa Leaves and Combination of Fe Tablets on the Increase of Hb in Pregnant Women with Anemia - Delfina, Rina; Helmiyetti, Helmiyetti; Maryani, Deni (Global Medical & Health Communication (GMHC), 2023)
Anemia during pregnancy can lead to complications during gestation, childbirth, and postpartum. The government recommends administering at least 90 Fe tablets to pregnant women to address this. Additionally, fulfilling nutritional needs is another strategy to combat anemia, with Moringa leaves emerging as a nutrient-rich food source known to elevate hemoglobin levels. This study investigated the impact of Moringa leaves and combined Fe tablet consumption on hemoglobin levels in anemic pregnant women. A quasi-experimental design incorporated pre-test and post-test evaluations with a control group in Bengkulu from June to November 2022. Purposive sampling yielded a cohort of 60 anemic pregnant women, divided equally into intervention and control groups. Data collected over two months were analyzed through univariate and bivariate methods using the Wilcoxon and Mann-Whitney tests at a 5% significance level. Findings indicated that the combination of Moringa leaves and Fe tablet significantly increased hemoglobin levels in pregnant women with anemia (p<0.05). Therefore, anemic pregnant women are encouraged to consume Moringa leaves as a potential measure to enhance their hemoglobin levels.